2016
DOI: 10.1117/1.jbo.21.7.075006
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating gastrointestinal stromal tumors from gastric adenocarcinomas and normal mucosae using confocal Raman microspectroscopy

Abstract: Gastrointestinal stromal tumors (GISTs) are the most common mesenchymal neoplasms of the gastrointestinal tract, and gastric adenocarcinomas are a common cancer worldwide. To differentiate GISTs from adenocarcinomas is important because the surgical processes for both are different; the former excises the tumor with negative margins, while the latter requires radical gastrectomy with lymph node dissection. Endoscopy with biopsy is used to distinguish GISTs from adenocarcinomas; however, it may cause tumor blee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…To enhance the application of confocal Raman microspectroscopy in differentiating, the Raman spectral data were further analyzed with the chemometrics methods as below. [49]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To enhance the application of confocal Raman microspectroscopy in differentiating, the Raman spectral data were further analyzed with the chemometrics methods as below. [49]…”
Section: Resultsmentioning
confidence: 99%
“…Orthogonal linear combinations to transform the original data into uncorrelated variables are termed PCs. [49] The PCs correspond to valuable "dimensions" of the data. Order of the PC corresponds to amount of information contained in a database relatively, for example, PC-1 express the highest amount of variation in the data.…”
Section: Pca and Pca-ldamentioning
confidence: 99%
“…A range of other studies also demonstrated the potential of Raman spectroscopy in diagnosing breast cancer in human and mouse breast tissues [89][90][91][92][93][94][95][96]. By exploiting the fingerprint region of the Raman spectrum and various machine learning techniques, Raman spectroscopy showed diagnostic potential for distinguishing cancerous tissues from normal tissues in brain cancer [56,[97][98][99][100], skin cancer [42,[101][102][103][104][105], gastrointestinal cancer [106][107][108][109], and lung cancer [110,111].…”
Section: Potential Applications In Clinical Cancer Diagnosismentioning
confidence: 97%
“…Cancer is one of the most common causes of death worldwide and RS makes it possible to diagnose undetected precancerous lesions in various organs, such as breast, skin, brain, gastrointestinal tract, heart, urinary, and reproductive tracts [40]. Hsu et al [41] investigated that confocal Raman microscopy distinguishes intestinal tumours from adenocarcinomas and normal, healthy organs. RS provides simple and immediate tissue identification during surgery, which allows for cancerous organs to be distinguished from healthy tissue.…”
Section: Disease Predictionmentioning
confidence: 99%